TEACHING DAILY SPEAKING BY USING TELEPHONE THROUGH QUESTION AND ANSWER TECHNIQUE TO THE FIRST GRADE STUDENTS OF DEPARTMENT OF ENGLISH TEACHING IKIP PGRI MADIUN IN THE SCHOOLING YEAR OF 2013/2014 - Fitra Pinandhita (English Teaching Journal : A Journal of English Literature, Language and Education, 2014)
The objectives of this research are: (1) to describe teaching daily speaking by using telephone through question and answer technique, (2) to describe the advantages and disadvantages of teaching daily speaking by using telephone through question and answer technique to the first grade students of Department of English Teaching IKIP PGRI Madiun in the schooling year of 2013/2014.In this research, the researcher takes five students of 1B from the Department of English Teaching IKIP PGRI Madiun as the sample. The researcher uses purposive sampling technique. To get the data, the researcher uses observation, interview, and documentation. In this research, analysis data is done by using descriptive analysis qualitative.The results of the research are: (1) the use of telephone through question and answer technique in teaching daily speaking to the first grade students of Department of English Teaching IKIP PGRI Madiun is divided into three steps, namely pre- activity, whilst-activity, and post-activity, (2) The advantages of using  telephone through question and answer technique in teaching daily speaking to the first grade students of Department of English Teaching IKIP PGRI Madiun are: the use of telephone through question and answer technique in teaching daily speaking can increase students’ scores, it makes enjoyable learning, students can focus on teaching learning process, the students have a good chance to practice with their friends in the group. This makes them more active in learning speaking, Last, the use of telephone through question and answer technique increases the students’ confidence. Meanwhile, the disadvantages are: the class becomes noisy when the students practice with their friends in the group, and some students have low vocabularies so that the students can not speak fluently.